Arduino Mega-Based Transporter Robot for Box Handling in a Maze Arena - Abdul Jalil; Suwatri Jura; A.Edeth Fuari Anatasya; Mursalim Sawawi; Pujianti Wahyuningsih (Journal of Applied Informatics and Computing, 2026)
The objective of this study was to develop a transporter robot designed to move boxes from one location to another within an Arduino Mega-based maze arena. The problems addressed by this transporter robot include autonomous navigation in the maze area, detection of boxes based on their colors, transferring boxes from one location to another, and climbing inclined surfaces. The method used to control the transporter robot was based on input from the TCS3200 color sensor and ultrasonic sensors, which were employed to detect box objects and navigate the robot. The Arduino Mega was used to process sensor data and control the robot according to the sensor inputs. A servo motor was utilized to actuate the robot arm and gripper, while DC motors were used to drive the wheels of the transporter robot. The results of this study indicate that the transporter robot was able to complete the mission of navigating the maze and transferring box objects to their designated locations, achieving a success rate of up to 70%, with an average mission completion time of 6.8 minutes, while unsuccessful mission attempts required up to 9.6 minutes.